Faktor Pengaruh Faktor Fundamental Terhadap Return Saham (Studi Pada Perusahaan Real Estate & Property Yang Terdaftar Di Bursa Efek Indonesia) - Yunita, Desi; Safitri, Alfiati; ', Andreas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to examine the effect of Debt to Equity Ratio ( DER ), Earning Per Share ( EPS ) and Return on Equity ( ROE ) to stock return. The object under study is a group of Real Estate & Property listed on the Indonesia Stock Exchange ( BEI ) in 2008-2010 with some of the criteria that have been described in previous chapters , so we get the end of the study sample as many as 20 companies of the group Real Estate & Property listed The Indonesia Stock Exchange ( IDX ) during the period 2008-2010.The analytical method used is multiple regression analysis in the t-test to see the effect of each independent variable on the dependent variable and partially in the coefficient of determination test to see how big the effect that the independent variable on the dependent variable. This study used secondary data from the Indonesia Stock Exchange with a sample of 20 companies from the group Real Estate & Property listed on the Indonesia Stock Exchange ( IDX ) during the period 2008-2010.The analytical method used was multiple regression. Based on the analysis , it is known that the independent variables have a significant influence on stock returns is earning per share with a P value of 0.046 at α = 0.05 level . The higher the EPS of a company, will have an impact on the higher the stock return of the firm. While other fundamental factors, namely Debt to Equity Ratio ( DER ) and Return on Equity ( ROE ) has no effect on stock returns. The coefficient of determination is 0.123 which shows the influence of the independent variables used in the model study on stock returns as the dependent variable was 12.3 % .Keywords : Debt to Equity Ratio ( DER ), Earning Per Share ( EPS ) , Return on Equity ( ROE ) and stock returns .